2012
DOI: 10.1111/j.1464-410x.2012.11195.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of American Society of Anesthesiologists scores in predicting urothelial carcinoma of the upper urinary tract outcome after radical nephroureterectomy: results from a national multi‐institutional collaborative study

Abstract: Study Type – Prognosis (cohort)Level of Evidence 2bWhat's known on the subject? and What does the study add?Upper urinary tract urothelial carcinoma (UUT‐UC) is a rare disease, usually treated by nephroureterectomy, occurring in a population with a median age of 70 years and with frequent tobacco use and other comorbidities. We know that the American Society of Anesthesiologists (ASA) score has prognostic value in urological oncology but this has not been assessed in UUT‐UC.Using a multi‐institutional French d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 26 publications
2
12
0
3
Order By: Relevance
“…For example, a large national multi-center collaborative study found that the ASA classification significantly correlated with CSS after RNU for UTUC. In this study, the 5-year CSS differed significantly between ASA 1, 2, and 3 patients (83.8%, 76.9%, and 70.6%, respectively), and there was a threefold higher risk of OM and CSM at 5 years for patients rated as ASA 3 compared with ASA 1 (25). In a recent study by Aziz et al (26), 4 comorbidity indices (ASA-PS, CCI, ACCI, and ECOG-PS) were compared with regard to recurrence-free survival (RFS), CSS, OS, and CIM.…”
Section: Discussionmentioning
confidence: 53%
“…For example, a large national multi-center collaborative study found that the ASA classification significantly correlated with CSS after RNU for UTUC. In this study, the 5-year CSS differed significantly between ASA 1, 2, and 3 patients (83.8%, 76.9%, and 70.6%, respectively), and there was a threefold higher risk of OM and CSM at 5 years for patients rated as ASA 3 compared with ASA 1 (25). In a recent study by Aziz et al (26), 4 comorbidity indices (ASA-PS, CCI, ACCI, and ECOG-PS) were compared with regard to recurrence-free survival (RFS), CSS, OS, and CIM.…”
Section: Discussionmentioning
confidence: 53%
“…14 A study that included 290 patients from the Memorial SloanKettering Cancer Center (MSKCC), New York, USA, with a median follow-up of 25 months reported similar findings. At baseline the radical and partial nephrectomy groups had similar mean preoperative serum creatinine levels (88.4 μmol/l and 86.63 μmol/l, respectively) and were comparable in terms of risk factors for renal insufficiency, including diabetes mellitus, hyper tension, age, American Society of Anaesthesiologists score for physical status, 26 and smoking status. At the end of the follow-up period, the mean postoperative serum creatinine level was significantly higher in the radical nephrectomy group than in the partial nephrectomy group (132.6 μmol/l versus 88.4 μmol/l, P <0.001).…”
Section: Nephrectomy and Ckdmentioning
confidence: 91%
“…Inversement, l'âge élevé a été rapporté comme un facteur pronostique corrélé à une survie spécifique (SSP) défavorable [8][9][10].…”
Section: Facteurs Pronostiques Cliniques En Rapport Avec Le Patientunclassified
“…Le retentissement de la maladie tumorale est évaluée par le score d'état général (score ECOG-Perfomance Status) ou par les comorbidités (score ASA) [10,11]. Ces deux systèmes de classification préopératoire sont apparus comme des facteurs pronostiques indépendants en termes de survie globale (SG) [10,11].…”
Section: Facteurs Pronostiques Cliniques En Rapport Avec Le Patientunclassified
See 1 more Smart Citation